تعلم الشعر العربي للطلبة الـمتخصصين باللغة العربية وآدابها عبر تطبيق "ديوان الشعر الإليكتروني" : دراسة تجريبية - تاج الدين، عبد البر (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
The main purpose of this study is to test “E-Diwan” mobile application as a form of educational experiment. “E-Diwan” app was developed by a team of researchers from the International Islamic University of Malaysia (IIUM) under a series of projects by the Malaysian Ministry of Higher Education (MoHE). The study reviewed previous literature related to mobile-learning (mLearning), mLearning for Arabic Language as well as for mLearning for poetry. The study then proceeds to frame out the procedures and aims of developing “E-Diwan” app. The details of the experimental field study that was conducted with participants from Arabic Language Department from IIUM will be discussed and the data results will be presented, on whether there were any significant differences between the results of the male and female participants after using “E-Diwan” app, as well as the steps of designing both; the questionnaire and the test that will be used to test participants' performance after using the app. The questionnaire collected data on user satisfaction with regards to the tools and the features of the app. Their feedback and suggestions for improvement were collated. The results confirmed that there were no significant differences between genders after using “E-Diwan” app and the results of the questionnaire were very positive indicating the acceptance and the eagerness for a modern educational instrument (mLearning). Some of the participants in the experimental study suggested improving some of the existing features of the app, such as voice and glossary. They also suggested providing video material and activities with each of the lessons provided. The study ended with some recommendations from the researcher based on his research, the results of the test and feedback from the participants.